Awareness of ADHD in primary care - French, Blandine (2021)
Despite ADHD impacting around 5% of children in the UK, GPs are ill-equipped to deal with this disorder. Over half of children with ADHD will continue experiencing symptoms into adulthood, and untreated and undiagnosed ADHD can strongly impact individuals throughout their lifetime. It is therefore vital that individuals access treatment and diagnosis at an early stage. The diagnosis pathway for ADHD is very complex. Specialist services in secondary care are responsible for ADHD diagnosis, most often following a referral from the patient’s GP. Without such referral, access to diagnosis and, in turn, access to care is often impossible. GPs' accurate understanding and awareness of ADHD is therefore primordial. Studies investigating GPs’ awareness of ADHD have found that GPs are ill-equipped to deal with individuals with ADHD, demonstrating a lack of knowledge and training, the presence of stigmas and misconceptions and a lack of clarity about their role. These barriers impact GPs’ ability to recognise ADHD in their patients and therefore referring to specialist services for assessment and treatment.